2009
DOI: 10.1021/ma9015938
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Mechanism and Regioselectivity of the Macromolecular Substitution Reactions of [NPCl2]n with Bifunctional Nucleophiles by a Combination of Quantum Mechanical and Molecular Dynamics Calculations

Abstract: A combination of molecular dynamics simulations and quantum chemistry calculations affords a good understanding of the reaction between [NPCl2] n and the bifunctional nucleophile aminophenol HO−C6H4−NH2 in THF solution and in the presence of alkali carbonates. This reaction is regiospecific at room temperature favoring the attack by the NH2 group, and only at higher temperatures the attack by the OH is activated. It is also explained why the reaction of HO−C6H4−NH2 with {[NP(O2C12H8)]1−x [NPCl2] x } n and Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This may not become a surprise as also other studies show a regioselectivity in the macromolecular substitution of bifunctional nucleophiles, with preferred substitution via an amine rather than an alcoholic hydroxyl. [46][47][48][49] In fact, the above suggested statistical mixture of both reaction topographies may even be favorable to promote plasticization, as suppression of regularity is attractive for suppressed crystallization and efficient plasticization. Also, whether the aminoethoxy ethanol NH 2 -(CH 2 ) 2 -O-(CH 2 ) 2 -OH reacts onto the phosphazene ring from its amine or hydroxyl group, the opposite peripheral hydroxyl or amine end groups can still allow hydrogen bonding with starch.…”
Section: Resultsmentioning
confidence: 99%
“…This may not become a surprise as also other studies show a regioselectivity in the macromolecular substitution of bifunctional nucleophiles, with preferred substitution via an amine rather than an alcoholic hydroxyl. [46][47][48][49] In fact, the above suggested statistical mixture of both reaction topographies may even be favorable to promote plasticization, as suppression of regularity is attractive for suppressed crystallization and efficient plasticization. Also, whether the aminoethoxy ethanol NH 2 -(CH 2 ) 2 -O-(CH 2 ) 2 -OH reacts onto the phosphazene ring from its amine or hydroxyl group, the opposite peripheral hydroxyl or amine end groups can still allow hydrogen bonding with starch.…”
Section: Resultsmentioning
confidence: 99%
“…On the micro scale, quantum mechanics (QM) simulations based on density functional theory 14,15 have been successfully applied to reveal the underlying reaction mechanisms that are difficult to obtain in experiments and to design reliable synthetic methodologies for diverse materials. 16 After using the correct experiments to identify the rate-determining reaction in thermal-oxidative aging, QM simulations can accurately calculate the free energy of the reaction. With molecular simulations, researchers can easily clarify the solubility and mobility of an antioxidant and the permeation process for O 2 during thermal-oxidative aging.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations help us obtain detailed insights about microstructures and provide direct quantitative information about the solubility parameters, mean square displacement, and other structural features of amorphous materials. On the micro scale, quantum mechanics (QM) simulations based on density functional theory , have been successfully applied to reveal the underlying reaction mechanisms that are difficult to obtain in experiments and to design reliable synthetic methodologies for diverse materials . After using the correct experiments to identify the rate-determining reaction in thermal-oxidative aging, QM simulations can accurately calculate the free energy of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies involving bifunctional molecules in substitution reactions with phosphazenes and polyphosphazenes involve diamines, amino‐alcohols and amino‐phenols that have one of their reactive sites protected, and deprotected after substitution. A theoretical study about the reactivity of p ‐aminophenol in polyphosphazene substitutions showed that lower energy is required to substitute the chlorine atoms through the nitrogen than through the phenolic oxygen, at room temperature and using THF as solvent . Therefore, this substitution would be expected to happen almost exclusively through nitrogen.…”
Section: Resultsmentioning
confidence: 99%